IMPLEMENTASI PEMBINAAN PENGAWAS SEKOLAH DALAM MENINGKATKAN KINERJA GTK MELALUI PEMANTAUAN STANDAR PTK PADA SEKOLAH DASAR DAERAH BINAAN KECAMATAN KOPANG KABUPATEN LOMBOK TENGAH TAHUN 2022 - AHMAD AHMAD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve gtk performance through monitoring ptk standards at elementary schools in the target area of ??the Kopang sub-district. The approach used in school supervision is a collaborative approach, by making the teachers and principals of the target schools work partners in achieving goals, with a personal approach of